Withering cash: Is Sweden ahead of the curve or just special? - Hanna Armelius; Carl Andreas Claussen; André Reslow (Sveriges Riksbank, 2020)
There is much in our increasingly digitized economies to suggest that the use of cash should fall. However, in almost all countries, it is constant or rising with a few notable exceptions. Sweden, in particular, displays a divergent development. In this paper, we explore the drivers behind this development. We use a data set consisting of 129 developed and developing countries and an extensive set of possible explanatory variables to estimate panel regressions for cash demand. In line with earlier studies, we find that economic development, demography, and the interest rate are important factors. A new finding is that our estimations point to a negative relationship between cash and corruption, and between cash and trust in government and financial institutions. However, this is not enough to fully explain the divergent development in Sweden. We therefore also discuss some recent events and policy measures in Sweden that seem to have accelerated the decline in cash during the last decade.
Keywords: E41; E42; E51; 330; Cash Demand; Currency in Circulation; Money